The Implementation of transformational Leadership and Teacher Work Engagement on Increasing Number of Students: Transformational Leadership, Principal, Teacher Work Engagement, Student Enrollment. - Manueke, Jessica Mellyta Lidya; Tung, Khoe Yao (Journal of Education Research, 2024)
The purpose of this study is to identify and describe the implementation of the roles of principals and teachers in increasing the number of school students in the coming year. Additionally, it aims to provide suggestions and ideas to schools, principals, and teachers on maximizing school promotion to increase the number of elementary school students. This research uses a qualitative study involving 11 participants at School House. Data triangulation was analyzed using coding (Strauss, 1990). The principal has implemented a transformational leadership style effectively in developing the school but has not been consistent due to limited infrastructure and resources, including facilities and teachers. This inconsistency is partly because teacher work engagement has not been the principal's main focus in efforts to increase the number of students at SD School House. The results of the study show that the increase in the number of students in the school is due to the implementation of transformational leadership in school operations.